Adrenergic regulation of lipolysis in situ at rest and during exercise. - Arner, P (1990)
The adrenergic regulation of lipolysis was investigated in situ at rest and during standardized bicycle exercise in nonobese healthy subjects, using microdialysis of the extracellular space in subcutaneous adipose tissue. The glycerol concentration was about two times greater in adipose tissue than in venous blood. At rest, the glycerol concentration in adipose tissue was rapidly increased by 100% (P less than 0.01) after the addition of phentolamine to the ingoing perfusate, whereas addition of propranolol did not alter the adipose tissue glycerol level. Glycerol in adipose tissue and plasma increased during exercise and decreased in the postexercise period. Propranolol in the perfusate almost completely inhibited the increase in the tissue dialysate glycerol during the exercise-postexercise period. Phentolamine, however, was completely ineffective in this respect. During exercise, the lipolytic activity was significantly more marked in abdominal than in gluteal adipose tissue; this was much more apparent in women than in men. Thus, in vivo lipolysis in subcutaneous adipose tissue is regulated by different adrenergic mechanisms at rest and during exercise. Alpha-adrenergic inhibitory effects modulate lipolysis at rest, whereas beta-adrenergic stimulatory effects modulate lipolysis during exercise. In addition, regional differences in lipolysis are present in vivo during exercise, which seem governed by factors relating to sex.